I.YUSUPOV SHÍǴARMALARÍNDA METAFORALARDÍŃ QOLLANÍLÍWÍ - Abdiev, A.; Ibraymova, M. (SCIENCE and SOCIETY, 2022)
This article is an in-depth study of the literary language and metaphors of the work of the Hero of Uzbekistan, People's Poet of Uzbekistan and Karakalpakstan Ibrayim Yusupov.